Cultural Diversity Training: The Necessity of Cultural Competence for Health Care Providers and in Nursing Practice. Issue 2 (April 2020) - Young, Susan; Guo, Kristina L.
Abstract : The purpose of this article is to discuss the need to provide culturally sensitive care to the growing number of diverse health care consumers. A literature review of national standards and research on cultural competency was conducted and specifically focused on the field of nursing. This study supports the theory that cultural competence is learned over time and is a process of inner reflection and awareness. The domains of awareness, skill, and knowledge are essential competencies that must be gained by health care providers and especially for nurses. Although barriers to providing culturally sensitive care exist, gaining a better understanding of cultural competence is essential to developing realistic education and training techniques, which will lead to quality professional nursing practice for increasingly diverse populations.